Perlindungan Hukum, Hak, dan Tanggung Jawab Debitur dalam Perjanjian Pinjam Meminjam Berbasis Aplikasi Digital di Indonesia: Perspektif Hukum dan Praktik Fintech - Andi Kurniawan; Siti Rahmawati; Budi Santoso (SIMPUL: Jurnal Ilmu Politik dan Hukum, 2026)
The development of financial technology (fintech) in Indonesia has spurred the emergence of digital app-based lending platforms that facilitate access to financing for the public. However, this convenience also poses legal risks for borrowers, particularly in cases of default. This study aims to analyze the legal protections, rights, and responsibilities of borrowers in digital app-based lending agreements in Indonesia, as well as to evaluate fintech practices regarding compliance with applicable regulations. The research methods employed include a legal-normative approach and case studies, analyzing legislation, decisions by the Financial Services Authority (OJK), and the operational practices of fintech platforms. The findings indicate that while fintech regulations have established a legal framework for debtor protection, gaps remain in the implementation of agreements and dispute resolution mechanisms that favor creditors. Debtors have the right to clear information, protection of personal data, and access to mediation mechanisms before legal action is taken. Meanwhile, the debtor’s responsibilities include fulfilling payment obligations and complying with the terms of the agreement. This study recommends strengthening debtor education, enhancing transparency in digital contracts, and implementing stricter oversight of fintech practices to improve legal certainty and consumer protection.